Investigating the Impact of Body Mass Index on Intraperitoneal Chemotherapy Outcomes in Ovarian and Fallopian Tube Cancer. Issue 6 (July 2016) - Davis, Michelle; Aviki, Emeline; Rauh-Hain, J. Alejandro; Worley, Michael; Berkowitz, Ross; Schorge, John; Muto, Michael; Clark Sisodia, Rachel; Horowitz, Neil; del Carmen, Marcela
Abstract : Objectives: The aim of this study was to investigate the impact of body mass index (BMI) on completion, complications, and clinical outcomes of intraperitoneal (IP) chemotherapy in patients with advanced-stage ovarian cancer. Methods: Patients with optimally cytoreduced International Federation of Gynecology and Obstetrics stage IIIC ovarian cancer treated with IP chemotherapy were retrospectively identified using an institutional review board–approved database. Clinical data were abstracted from the longitudinal medical record. Survival estimates were calculated using the Kaplan-Meier method. Results: Ninety-two patients (35.5%) completed at least one cycle of IP chemotherapy. For these patients, there was no difference in histology, surgical complexity, or degree of cytoreduction based on BMI. Sixty-five percent of normal weight, 70% of overweight, and 59.1% of obese women completed 6 cycles ( P = 0.697). There was also no significant difference in IP chemotherapy complications ( P = 0.303). Body mass index had no impact on disease-free survival ( P = 0.44) or overall survival, with a median overall survival of 68.5 months for normal weight, 65.9 months for overweight, and 61.7 months for obese women ( P = 0.25). However, on multivariate analysis, obesity had an odds ratio of 2.92 ( P = 0.02) for mortality. There was a trend toward treatment with intravenous chemotherapy (84.2%) over IP (15.8%) in patients with class II obesity ( P = 0.06). Discussion: There was no difference in completion of IP chemotherapy or complications with respect to BMI; however, there was a trend away from treatment with IP therapy in extreme obesity. These data suggest that IP chemotherapy is feasible in obese patients without incurring increased morbidity.